Biomarkers for hepatitis B virus replication: an overview and a look to the future. (1st December 2020) - Li, Feng-Cai; Li, Yue-Kai; Fan, Yu-Chen
ABSTRACT: Introduction: Hepatitis B virus (HBV) infection is a major public health issue but there are no powerful drugs to eradicate the virus. HBV markers including HBsAg, HBcrAg, HBV RNA, HBcAb, and HBV DNA are becoming promising biomarkers to reflect the natural phases of chronic HBV infection and predict the outcome of anti-HBV treatment. Areas covered: The authors summarized the biomarkers of HBV replication and presented the current advances of these biomarkers on predicting the outcome of anti-HBV treatment and identifying the progression of chronic HBV infection. Expert opinion: HBsAg, HBcrAg, HBV RNA, HBcAb, and HBV DNA are noninvasive and feasible biomarkers for monitoring the process of anti-HBV therapy and predicting the progress of HBV infection. However, there are still no strong biomarkers with high sensitivity and specificity for clinical application. Combination of two or more HBV biomarkers, new technique for measuring HBV cccDNA, and searching novel HBV biomarkers are essential for anti-HBV treatment in the future.